Molecular Heterogeneity in Localized Diffuse Large B-Cell Lymphoma - Qin, Wei; Fu, Di; Shi, Qing; Dong, Lei; Yi, Hongmei; Huang, Hengye; Jiang, Xufeng; Song, Qi; Liu, Zhenhua; Cheng, Shu; Huang, Jinyan; Wang, Li; et al. (Frontiers in Oncology, 2021)
Clinical and molecular characteristics of localized diffuse large B-cell lymphoma (DLBCL) with single nodal (SN) or single extranodal (SE) involvement remain largely elusive in the rituximab era. Clinical data of 181 patients from a retrospective cohort and 108 patients from a phase 3 randomized trial NHL-001 (NCT01852435) were reviewed. Meanwhile, genetic aberrations, gene expression pattern and tumor immunophenotype profile were revealed by DNA- and RNA-sequencing of 116 and 53 patients, respectively. SE showed similar clinicopathological features as SN patients, except for increased percentage of low-intermediate risk National Comprehensive Cancer Network-International Prognostic Index. According to the molecular features, increased MPEG1 mutations were observed in SN patients, while SE patients were associated with upregulation of TGF-β signaling pathway and downregulation of TCR signaling pathway. SE patients also presented immunosuppressive status with lower activity of killing of cancer cells and recruiting dendritic cells. Extranodal involvement had no influence on progression-free survival (PFS) or overall survival (OS) in localized DLBCL. Serum lactate dehydrogenase >3 upper limit of normal was an independent adverse prognostic factor for OS, and ATM mutations were related to inferior PFS. Although overall prognosis is satisfactory, specific clinical, genetic and microenvironmental factors should be considered for future personalized treatment in localized DLBCL.